37.7k views
22 votes
Solve for x

\bold{x {}^(2) + 5x + 6 = 0}

ty! ~​

User Positivew
by
4.6k points

2 Answers

10 votes

Answer:

  • x = -2
  • x = -3

Explanation:


\bf {x}^(2) + 5x + 6 = 0

Write the equation in factored form.


\bf (x + 2)(x + 3) = 0

Separate equations, and set each factor to zero.


\bf x + 2 = 0


\bf x + 3 = 0

Rearrange and isolate the variable to find the solutions


\bf x = - 2


\bf x = - 3

------------------------------------

User Bob Stine
by
5.1k points
8 votes

Answer:

x=-3 x=-2

Explanation:

x^2 +5x+6 =0

We need to factor the equation

What two numbers multiply to 6 and add to 5

3*2 = 6

3+2 =5

(x+3)(x+2)

Using the zero product property

x+3 =0 x+2 =0

x=-3 x=-2

User Thefourtheye
by
5.2k points